Optimising commercial cleaning services based on customer expectations and their fulfilment: An empirical analysis with the means-end theory of complex cognitive structures - Hendrik Godbersen; Daniel Wenzel (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2022)
This paper aims to shed light on the customer expectations towards commercial cleaning services providers and their fulfilment so that options for improving such services can be deduced. To this end, we develop a comprehensive and threetiered assessment model of commercial cleaning services and apply it in an empirical study with 304 participants from organisations, using external cleaning services. The methodological basis of our research is the Means-End Theory of Complex Cognitive Structures. Amongst other results, we could show that commercial cleaning services providers should use the current pricing strategy as a strength and can build on this, whilst they are advised to improve the quality of their service offerings with a high priority. With a lower priority, commercial cleaning services providers should improve the competencies of their staff, the direct customer interaction and the communication of their services. This indicates that commercial cleaning services providers should firstly focus on the results of their services and then develop their service processes and communication on this basis.
Keywords: 650; Means-End Theory; Commercial Cleaning Services